2003
DOI: 10.1002/maco.200303735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H2S on metal dusting of iron

Abstract: A review is given on the effect of H 2 S on metal dusting of iron which has been studied by gas carburisation in CO-H 2 -H 2 O-H 2 S and CH 4 -H 2 -H 2 S mixtures at 500 and 700 8C.The presence of H 2 S in carburising gas atmospheres leads to sulphur adsorption on the iron surface, which retards carbon transfer. Segregation experiments and surface analyses have shown that sulphur segregates (and thus adsorbs) on cementite surfaces as well as on iron surfaces. The adsorbed sulphur also suppresses graphite nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Grabke and co-workers have observed that a small concentration of H 2 S in a CO/H 2 gas mixture can retard the metal dusting process. 74,75 This is likely to be due to the facile deposition of S atoms that block the surface sites for CO adsorption and/or dissociation (i.e., S poisons the surface). Our prediction of strong bonding between Fe and S (∼6 eV) is consistent with this idea.…”
Section: H 2 S Dissociationmentioning
confidence: 99%
“…Grabke and co-workers have observed that a small concentration of H 2 S in a CO/H 2 gas mixture can retard the metal dusting process. 74,75 This is likely to be due to the facile deposition of S atoms that block the surface sites for CO adsorption and/or dissociation (i.e., S poisons the surface). Our prediction of strong bonding between Fe and S (∼6 eV) is consistent with this idea.…”
Section: H 2 S Dissociationmentioning
confidence: 99%
“…3 Since thermal decomposition of NH 3 as well as decomposition of (metastable) iron nitrides are slow, 4 transfer of nitrogen from the gas atmosphere into the specimen can be described by the following heterogeneous chemical equilibrium: of nitrogen dissolved in the solid at the surface (assumed to be in equilibrium with the gas atmosphere) obey: denotes the socalled nitriding potential, where p NH 3 and p H 2 are the partial pressures of ammonia and hydrogen in the gas atmosphere. Hence, according to Eq.…”
Section: Thermodynamics Of Gaseous Nitrocarburisingmentioning
confidence: 99%
“…3 At atmospheric pressure and at the applied treatment temperatures, N 2 does not react with solid iron; it can be regarded as an inert gas. 4 This implies that the reaction NH 3 1 2 N 2 þ 3 2 H 2 is necessarily not in equilibrium in the gas phase, which is assured by a sufficiently large gas flux though the furnace (cf. Sect.…”
Section: Thermodynamics Of Gaseous Nitrocarburisingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of cementite compound layers it turns out that the nitrogen (and carbon) diffusion into the substrate is strongly decelerated; cementite acts as a diffusion barrier for [15] and carbon [16]. Nonetheless, although nitrogen transport through cementite is decelerated, it is shown in this paper that a certain time-dependent amount of nitrogen is transported through the cementite into the ferrite substrate, leading to an increase of the nitrogen content in (and the hardness of) the ferrite substrate.…”
Section: Introductionmentioning
confidence: 99%